Property management of government building case study: police department Selangor Police Contingent Headquaters / Mohd Zaidi Razali - Razali, Mohd Zaidi (2010)
Property assets such as land and building are a key resource for all types of organizations, including public sectors. For the last two decades positives effects of good property management have received increased attention as the stock of new buildings costing billions of ringgit are being put into operation. In private sector, this attention is due largely to the recognition of the significant contribution property makes to ultimate success or failure of a business and recognition of strategic importance of property to a company's financial structure. While within public sector or government buildings organization property can be considered as having financial contribution and effect'upon annual financial statements, asset base and as well as on resale values in case of privatizations of any public entities. Therefore property resources, in the same way as human, financial and information resources contribute to the success of these organizations and need to be effectively and efficiently managed. These property assets have to be professionally managed to ensure that the asset value is maintained. It is acknowledged that not only is a large amount of capital devoted to these property assets, they can also add value to an organization through effective and often creative management. However, do public sector organizations in Malaysia recognize that property, both raw and buildings are valuable assets? Landed professionals have been calling for the need to managed public sector property more professionally for a long time and its also stated in the book that write by Dass, 1985, Marbeck, 1988, Singh, 1994 and 1996, and Mahadi, 1998. Hence, realizing the importance of property to public sector organizations, this paper will discuss the functions of public property management, focusing on the management of office building. In doing so, this research will explore the need for property management and also can be discuss the management practice in public sector property management.